2017
DOI: 10.1111/1365-2745.12844
|View full text |Cite
|
Sign up to set email alerts
|

Soil biotic quality lacks spatial structure and is positively associated with fertility in a northern grassland

Abstract: Abstract1. When placing roots in the soil, plants integrate information about soil nutrients, plant neighbours and beneficial/detrimental soil organisms. While the fine-scale spatial heterogeneity in soil nutrients and plant neighbours have been described previously, virtually nothing is known about the spatial structure in soil biotic quality (measured here as a soil Biota-Induced plant Growth Response, or BIGR), or its correlation with nutrients or neighbours. Such correlations could imply trade-offs in root… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 87 publications
1
22
0
Order By: Relevance
“…However, at least within patches, the soil biotic quality experienced by plants appears to be equally variable within and outside B. inermis –invaded areas (Chagnon et al. ). The consequences of biotic homogenization within and across sites due to B. inermis invasion should be further investigated, as they could lead to losses in ecosystem function (Zak et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, at least within patches, the soil biotic quality experienced by plants appears to be equally variable within and outside B. inermis –invaded areas (Chagnon et al. ). The consequences of biotic homogenization within and across sites due to B. inermis invasion should be further investigated, as they could lead to losses in ecosystem function (Zak et al.…”
Section: Discussionmentioning
confidence: 99%
“…Piper et al (2015b) found microbial communities to be more homogeneous among B. inermis-invaded areas, compared to uninvaded areas. However, at least within patches, the soil biotic quality experienced by plants appears to be equally variable within and outside B. inermis-invaded areas (Chagnon et al 2018). The consequences of biotic homogenization within and across sites due to B. inermis invasion should be further investigated, as they could lead to losses in ecosystem function (Zak et al 2003, Lamb et al 2011, Hautier et al 2018) and increase the vulnerability of these communities to large-scale disturbances (Olden et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In the high‐nutrient‐heterogeneous soil treatment, fertilizer was distributed along the outside of the mesocosm with no nutrients placed in the centre of the mesocosm (low‐quality patch). For the initial microbial suppression treatment, soil was autoclaved at 121°C for 3 hr (Chagnon, Brown, Stotz, & Cahill, ) prior to nutrient addition to reduce any positive effects of sterilization on nutrient concentrations (Powlson & Jenkinson, ). Although autoclaving soil prior to nutrient addition cannot fully control for differences in nutrient concentrations among sterilized and non‐sterilized treatments, this should be minimized here due to the low fertility of the soil mixture (Powlson & Jenkinson, ).…”
Section: Methodsmentioning
confidence: 99%
“…Smooth brome invasion into intact native grasslands has been extensively studied [9][10][11][12][13][14][15][16][17] . Smooth brome invasion radically changes plant community structure 15,16 , and subsequently causes changes in soil nutrient cycling and soil microbial community structure and function [9][10][11]18,19 .…”
Section: Background and Summarymentioning
confidence: 99%